Design and Realization of SDN-Based IPv6 Transition Technology - Qiong Sun; Chongfeng Xie; Huiling Zhao; Xushan Lu; Shucheng Liu (Dianxin kexue)
SDN-based IPv6 transition technology was researched. A solution on how to introduce SDN-based IPv6 transition technology in operator network was firstly proposed, including application scenario, requirements, overall architecture, key technologies and major deployment requirement. This technology is quite important for operators to introduce SDN-based IPv6 transition in operator network.